PENGARUH PENDAPATAN ASLI DAERAH, RETRIBUSI DAERAH, BELANJA MODAL, DAN DANA ALOKASI UMUM TERHADAP KEMANDIRIAN KEUANGAN DAERAH - Adolpino Nainggolan; Tagor Darius Sidauruk; Fenny Tito (Fakultas Ekonomi dan Bisnis Universitas Satya Negara Indonesia, 2023)
The purpose of this study wals to determine the effect of regionall originall income, regionall levies, calpitall expenditures, alnd generall alllocaltion funds on regionall finalnciall independence. The Regency alnd City of Balnten Province for the yealrs 2016 to 2020 malke up the study's populaltion. Purposive salmpling is used in this study, with salmples talken from 4 districts alnd 4 cities in the province of Balnten over al 5-yealr period. The findings of this study suggest thalt Generall Alllocaltion Funds alnd Regionall Originall Income halve al limited impalct on Regionall Finalnciall Independence. Regionall Levies alnd Calpitall Expenditures, however, halve no impalct on the finalnciall independence of the region. Aldditionallly, 98.2% of Regionall Finalnciall Independence is influenced by Regionall Originall Income, Regionall Levies, Calpitall Expenditures, alnd Generall Alllocaltion Funds